Determining the prevalence of dietary supplement consumption among Ardabil University students and related factors, 2014 - Fattahzadeh-Ardalani, Ghasem; Farzaneh, Esmaeil; Fathi, Afshin; Molaei, Behnam; Valizadeh, Mehdi (International Journal Of Community Medicine And Public Health, 2017)
Background: Dietary supplements (DS) are commercially available products that are consumed as an addition to the usual diet. But little data are available on their use by sub-populations such as college students. Since college students share a variety of characteristics and similar lifestyles, their DS use may differ from the general population. In this study, we aimed to investigate the prevalence of food supplements usage, factors associated with DS usage and reasons for DS usage among a group of university students in Ardebil-Iran. Methods:250 College students from Ardabil universities were selected by random sampling in year 2014. The Survey questionnaire used in this study included Part I: demographic characteristic, Part II: types and frequency of dietary supplements used. Supplements were classiﬁed using standard criteria. Logistic regression and X2 test analyses examined relationships between demographic, lifestyle factors and dietary supplements use. Results: The frequency of food supplements usage between students was 66.8% and there was a significant relationship between age, gender, marital status, BMI, income and DS usage, while there was no significant relationship between educational level and DS usage. The frequency of food supplements usage in students with 19 to 35 years and married females was high. After controlling the confounding factors, marital status variable was the factor that influenced the usage of dietary supplements so that, despite the high level of food supplements usage in males, married people's tendency to supplements usage in married people was 1.5 times more than the singles. Conclusions:Results showed that the use of dietary supplements is considerably high among students. Doing further study on the general population can be necessary.